Association between CT-Detected Coronary Artery Calcification and Serum Homocysteine Level in Asymptomatic Adults - Mishal Safdar; Sumaira Aslam; Wajeeha Anwar; Syed Liaquat Ali; Khawar Anwar; Shabzain Ishrat (Pakistan Journal of Health Sciences, 2026)
The association between CT-detected CAC and serum homocysteine levels in asymptomatic adults may provide valuable insights into the pathophysiological mechanisms underlying subclinical atherosclerosis. Objectives: To determine the association between CT-detected coronary artery calcification and serum homocysteine levels in the asymptomatic Pakistani population. Methods: A cross-sectional analytical study was conducted on 384 asymptomatic Pakistani adults aged 30–65 years. Coronary artery calcification was assessed using non-contrast CT (Agatston score), and serum homocysteine levels were measured. Associations were analyzed using descriptive statistics and Pearson correlation using SPSS. Results: Among 384 asymptomatic adults, coronary artery calcification (CAC) was detected in 41.7% of participants. Individuals with CAC had significantly higher serum homocysteine levels compared to those without calcification (p < 0.001). Serum homocysteine increased progressively with CAC severity and showed a significant positive correlation with CAC score. Statistical testing demonstrated that serum homocysteine was significantly associated with coronary artery calcification after adjusting for traditional cardiovascular risk factors. Conclusions: Elevated serum homocysteine was independently associated with the presence and severity of CT-detected coronary artery calcification in asymptomatic adults. These findings suggest that homocysteine may serve as a useful biomarker for identifying individuals at increased risk of subclinical coronary atherosclerosis.